DISTRIBUTION OF ABO AND RH-D BLOOD GROUPS IN ALJUFRA- LIBYA (Journal of Academic Research, 2021)
The study of distribution of blood group is very important for blood banks and transfusion services that could contribute to the patients' health care. This study to Known the distribution of blood group ABO in Aljufra Libya. In addition, performed on the five main cities of Aljufra Libya namely, Waddan, Hoon, Soknah, Zilla and Alfugha. It was found that, blood group O was the most common of the ABO blood group system in the Aljufra Libya, nevertheless AB blood group was lower rare, and Rhesus D positive was more common than Rhesus D negative phenotype. The distribution of ABO blood group varies from one population to another. In a study, it was show that Blood group O was the highest, then blood group A and B finally AB.